Afrocubanisme au Québec : La rumba guaguanco - Cano, Jocelyn (MUSICultures, 1990)
Hughes Jocelyn Cano compares Cuban music in Montréal and Cuba focusing on a specific genre, the rumba guaguanco.

Haitian Popular Music in Montreal: The Effects of Acculturation - Juste-Constant, Voegeli; Shepherd, John (Popular Music, 1990)